THE EFFECT OF TAX PLANNING, INTELLECTUAL CAPITAL, AND ACCOUNTING CONSERVATIONS ON EARNINGS MANAGEMENT (STUDY OF CONSUMER GOODS SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2019- 2022) - Setiawan , Wahyu; Maharani , Rieska; Sari, Tyasha Ayu Melynda (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study aims to determine the effect of tax planning, intellectual capital, and accounting conservatism on earnings management of consumer goods sector companies listed on the Indonesia Stock Exchange in 2019-2022. The research method uses multiple linear regression analysis with a quantitative approach. This study used a sample of 104 data with sampling using the purposive sampling technique. The measuring instrument used is Statistical Package for the Social Sciences (SPSS) version 25. The results showed that simultaneously tax planning, intellectual capital, and accounting conservatism had no effect on earnings management with a significance value of 0.460. The partial test results show that tax planning has a significant positive effect on earnings management with a significance value of 0.028 based on agency theory, where companies try to pay the minimum possible tax to the government so as not to reduce the profit earned in the current year. Intellectual capital has no effect on earnings management with a significance value of 0.730. This is because in the Value Added Intellectual Coefficient (VAIC), employee expenses are not counted as costs. Accounting conservatism has no effect on earnings management with a significance value of 0.704; this is due to the implementation of the International Financial Reporting Standards (IFRS) guidelines in Indonesia. The coefficient of determination shows a value of 0.024, indicating that the variables included in the model are able to influence earnings management by 2.4%.